Administrative and economic dimensions of regionalization: case of Leningrad Province and North-Western Federal District of Russia - Rybakov, Felix Fedorovich; Sutyrin, Sergei Felixovich; Lisitsyn, Nikita Evgenjevich (Louvain-la-Neuve: European Regional Science Association (ERSA), 2003)
The North-Western Federal District (NWFD) was created in 2000 within the framework of administrative and territorial division reforming. NWFD appeared together with 6 other districts: Central, Privolzhski, Southern, Urals', Siberian and Far Eastern. The District included 2 economic regions: North-Western and Northern and united 11 Federation Units: Kaliningrad, Leningrad, Pskov, Novgorod, Vologda, Murmansk and Arkhangelsk provinces, Karelia and Komi Republics, Nenets Autonomous District and Saint-Petersburg._ According to many indicators North-West Federal District of Russia is a leader of NWFD, leaving behind even Saint-Petersburg (if we compare investment attractiveness, especially for FDI, both domestic and foreign). During 1999 - 2000 several big investment projects started in the Province. The Province's only real competitor among NWFD regions is Novgorod region which also formed an ?oasis' of favorable investment climate within its boundaries._ Economic and geographical significance of Leningrad Province for NWFD and whole Russia is based on transport infrastructure, which develops actively on its territory. The infrastructure includes seaports and railroads that serve as transit bridges between Russia and European countries. That was the reason for the Province's participation in main investment projects in NWFD implemented during the last years, such as creation of Baltic Pipeline System (BPS). BPS project gained national significance; besides, it gave a prominent impact to NWFD fuel industry development. Due to BPS fuel sector companies that operate in oil and gas provinces of Arkhangelsk Province, Komi Republic and Barents and Kara Sea got direct access to seaports on Russian territory._ Interregional relations are developing in other industries as well. New machine-building companies of Leningrad Province start to co-operate with suppliers from other NWFD regions. For example, ?Ford-Vsevolozhsk? company signed a contract with Bor glass factory on automobile glass supplies._ In NWFD interregional ...